Peningkatan Keterampilan Membaca Nyaring Melalui Metode Latihan Terbimbing pada Siswa Kelas III SD Negeri 115 Kabupaten Halmahera Selatan - Muti Umanahu; Wachyudi Eksan; Julaini Jainudin (Jurnal Ilmiah Wahana Pendidikan, 2022)
Given the importance of the role of reading for student development, the way teachers teach reading must choose appropriate and correct teaching strategies so that it is easy for children to understand. So far, the way teachers deliver to third grade students at SD Negeri 115, South Halmahera Regency is not appropriate. In teaching both methods and approaches, the results obtained by class III students are relatively low and children are less interested in teaching Indonesian. From the various problems above, the guided training method is felt to be very instrumental in helping the process and the gradual achievement of learning objectives. In this study, the researcher describes the Improvement of Reading Aloud Skills Through Guided Practice Methods for Third Grade Students of SD Negeri 115, South Halmahera Regency. The research method that will be used is Classroom Action Research (CAR). The subjects in this study were third grade students of SD Negeri 115, South Halmahera Regency, with a total of 20 students consisting of (9 male students and 11 female students).